2008
DOI: 10.1530/rep-07-0415
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in messenger RNA profiles of bovine endometrium during the oestrous cycle

Abstract: During the oestrous cycle, the bovine endometrium exhibits characteristic morphological and functional changes, which are mainly induced by progesterone (P 4 ), oestrogens and oxytocin. We studied the response of the endometrium to this changing hormonal environment at the transcriptome level using a custom-made cDNA microarray. Endometrium samples were recovered from Simmental heifers on days 0 (oestrus), 3.5 (metoestrus), 12 (dioestrus) and 18. The latter group was divided into animals with high (late dioest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 71 publications
6
86
1
3
Order By: Relevance
“…A twin pregnancy was diagnosed if 2 embryonic discs were detected. Endometrial tissue samples were collected, preserved, and processed for isolation of RNA as previously described (38).…”
Section: Methodsmentioning
confidence: 99%
“…A twin pregnancy was diagnosed if 2 embryonic discs were detected. Endometrial tissue samples were collected, preserved, and processed for isolation of RNA as previously described (38).…”
Section: Methodsmentioning
confidence: 99%
“…A variety of studies in cattle, including studies from our own group (Forde et al, 2009 and, evaluated genes expressed in the endometrium of the uterus during selected stages of the oestrous cycle and pregnancy (Bauersachs et al, 2005(Bauersachs et al, , 2006Mitko et al, 2008;MansouriAttia et al, 2009). However, data on gene expression during the post-hatching embryonic stages in cattle are sparse and, apart from a few exceptions, typically deal with candidate genes rather than being global in nature (Ushizawa et al, 2004;Hue et al, 2007;Degrelle et al, 2011).…”
Section: Gene Expression In the Conceptusmentioning
confidence: 99%
“…Plasma P4 concentrations gradually increase with the formation of the CL, reaching a maximum value in the mid-dioestrus phase between Day 10 to 14 of oestrous cycle (Kastelic et al, 1990, Siqueira et al, 2009. Larger variations in expression of immune genes have been observed in endometrial transcriptome profile from cows in mid-dioestrus (Day 12) compared to early metoestrus (Day 3.5) (Mitko et al, 2008). However, in this case, the difference in P4 concentration was not sufficient to stimulate changes in gene expression of these targeted genes.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, endometrial transcriptome studies (Bauersachs et al, 2005, Mitko et al, 2008, Forde et al, 2011a identified genes differentially expressed during the oestrous cycle. These genes are especially related to cell motility, cytoskeleton, extracellular matrix (ECM), ECM remodelling, and cell growth are differentially expressed.…”
Section: Embryo Mortality and Endometrial Receptivitymentioning
confidence: 99%